Genetic analysis in cashew (Anacardium occidentale L.) - Ushavani, D.; Jayalekshmy, V.G. (Journal of Plantation Crops, 2009)
Genetic analysis in cashew with 12 genotypes and 14 morphological traits revealed that the genotypes showed significant variation with respect to all characters except number of primary branches. Number of perfect flowers m-2, number of nuts m-2, apple weight, nut weight and kernel weight provided a clear separation of the genotypes. Number of perfect flowers m-2 and number of nuts m-2 had high heritability indicating the reliability of these traits in selection. Number of nuts m-2 also had significant positive correlation and direct effect on yield. Apple weight showed significant negative correlation and significant negative direct effect with yield. Cluster analysis could group the accessions into four clusters. Cluster I (Sulabha, Priyanka and P-3-2) and Cluster II (Mdk-1, AKM-1 and K-22-1) were the most divergent. Members of these two clusters can be utilized for hybridization in all possible combinations to yield superior cashew hybrids.